Methods in Contemporary Linguistics - Ender, Andrea; Leemann, Adrian; Wälchli, Bernhard (Trends in Linguistics. Studies and Monographs [TiLSM], 2012)
The present volume is a broad overview of methods and methodologies in linguistics, illustrated with examples from concrete research. It collects insights gained from a broad range of linguistic sub-disciplines, ranging from core disciplines to topics in cross-linguistic and language-internal diversity or to contributions towards language, space and society. Given its critical and innovative nature, the volume is a valuable source for students and researchers of a broad range of linguistic interests.